Eksces i tragizm: „Noc Walpurgii, czyli Kroki Komandora” Wieniedikta Jerofiejewa - Beata Waligórska-Olejniczak (Studia Rossica Posnaniensia)
The article presents Venedikt Erofeev’s Walpurgisnacht, or the Steps of the Commander in the context of European transavantgarde, American art (e.g. Andy Warhol’s traumatic realism) and the vital literary concepts of the end of the 20th century. The category of shock is here regarded as a postmodern equivalent of the ancient notion of catharsis. The focus of the artistic reality in Erofeev’s text seems to be on the tragic conflict between life and death and on being in transition, which reveals the real purpose of human existence.